A new pentafluorothio-substituted curcuminoid with superior antitumor activity - Linder, Benedikt; Köhler, Leonhard H. F.; Reisbeck, Lisa; Menger, Dominic; Subramaniam, Dharmalingam; Herold-Mende, Christel; Anant, Shrikant; Schobert, Rainer; Biersack, Bernhard; Kögel, Donat (Biomolecules, 2021)
A new and readily available pentafluorothiophenyl-substituted N-methyl-piperidone curcuminoid 1a was prepared and investigated for its anti-proliferative, pro-apoptotic and cancer stem cell-differentiating activities against a panel of human tumor cell lines derived from various tumor entities. The compound 1a was highly anti-proliferative and reached IC50 values in the nanomolar concentration range. 1a was superior to the known anti-tumorally active curcuminoid EF24 (2) and its known N-ethyl-piperidone analog 1b in all tested tumor cell lines. Furthermore, 1a induced a noticeable increase of intracellular reactive oxygen species in HT-29 colon adenocarcinoma cells, which possibly leads to a distinct increase in sub-G1 cells, as assessed by cell cycle analysis. A considerable activation of the executioner-caspases 3 and 7 as well as nuclei fragmentation, cell rounding, and membrane protrusions suggest the triggering of an apoptotic mechanism. Yet another effect was the re-organization of the actin cytoskeleton shown by the formation of stress fibers and actin aggregation. 1a also caused cell death in the adherently cultured glioblastoma cell lines U251 and Mz54. We furthermore observed that 1a strongly suppressed the stem cell properties of glioma stem-like cell lines including one primary line, highlighting the potential therapeutic relevance of this new compound.